Theoretical investigations on the effects of mutations in important residues of NS1B on its RNA-binding using molecular dynamics simulations. (June 2022) - Xu, Dan; Zheng, Qing-Chuan
Abstract: NS1B protein plays an important role in countering host antiviral defense and virulence of influenza virus B, considered as the promising target. The first experimental structure of the NS1B protein has recently been determined, was able to bind to double-stranded RNA (dsRNA). However, few studies attempt to investigate the RNA-binding mechanism of the NS1B. In this study, we provide our understanding of the structure-function relationship, dynamics and RNA-binding mechanism of the NS1B protein by performing molecular dynamics simulations combined and MM-GBSA calculations on the NS1B-dsRNA complex. 12 key residues are identified for RNA-binding by forming hydrogen bonds with the. Our results also demonstrate that mutations (R156A, K160A, R208A and K221A) can cause the local structure changes of NS1B CTD and the hydrogen bonds between NS1B CTD and RNA disappearance, which may be the main reasons for the decrease in RNA-binding affinity. These results mentioned will help us understanding the RNA-binding mechanism and could provide some medicinal chemistry insights chances for rational drug design targeting NS1B protein. Graphical abstract: Image 1 Highlights: Molecular dynamics simulations of the NS1B protein and four mutants with dsRNA. The reasons for the decrease of RNA-binding affinity caused by mutations were discussed at the molecular level. The introduction of negative charged residue is a key factor in potential antiviral drugs design for NS1B protein.